Fibre technologies in Indigenous Australia: Evidence from archaeological excavations in the Kimberley region. Issue 2 (4th May 2022) - Balme, Jane; O'Connor, Sue; Maloney, Tim Ryan; Akerman, Kim; Keaney, Ben; Dilkes-Hall, India Ella
Abstract: The extent to which fibre technology was used in the past is difficult to assess because soft organic remains rarely preserve well. The oldest direct evidence for twisted fibre cordage is dated to between 41 and 52 ka in western Eurasia but indirect evidence suggests that it may have a much greater antiquity. The diverse use of string made from fibres of plants, animal and human hair by Indigenous Australians is well documented but poorly represented in archaeological sites. No fibre remains have been recovered from Pleistocene contexts and they are only rarely recorded in later deposits, usually as isolated fragments. Nineteen pieces of twisted fibre recovered from deposits in two limestone caves, Carpenter's Gap 1 and Riwi in the southern Kimberley, are made from a variety of raw materials and manufacturing techniques. These same techniques and raw materials are documented in anthropological and historical records and in museum collections, demonstrating a continuity of spun fibre practice from the Mid-to-Late Holocene to the present. A comparison of the archaeological twisted fibres with Kimberley objects incorporating string held in the Western Australian Museum, provides further insight into the technology used by Indigenous Australians before the arrival of Europeans.